Challenges and limitations in implementing the cost system in the City Hall of Fortaleza - Silva, Angeliana Ferreira da; Steindorfer , Igor Barroso; Bringel, Juliana Holanda Farias de Araripe; Nobre, José Geovanildo; Vasconcelos, Alessandra Carvalho de (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
The adoption of a cost system by the public administration is imposed by Brazilian legislation. Thus, this research investigated the challenges and limitations faced during the implementation of the Cost Information System (SIC) in the City Hall of Fortaleza (PMF). A questionnaire was applied to managers and technicians who participated in the implementation of the SIC in the PMF. The results indicate that the integration and customization of systems and aspects related to organizational structures are the main challenges of the PMF, while the main limitations to the implementation of the SIC are related to the scope and team involved. The research expands the discussions on cost management, by providing evidence that helps the decision-making process in the public sector.